Optimization of Railway Equipment Maintenance Plan Based on Intelligent Patrol Inspection System - MA Yunlong (Kongzhi Yu Xinxi Jishu)
In order to overcome the shortcomings of poor accuracy, control absence and difficult implementation in the process of conventional railway equipment maintenance, this paper proposes an intelligent patrol inspection system solution, which integrates intelligent inspection and maintenance collectors, intelligent patrol inspection instruments and video monitors, and leverages microcontrollers, host computers, networked communication and other advanced technologies, as well as the developed equipment maintenance software,to realize the information-based and intellectualized patrol inspection on equipment.Thus this system functions to generate maintenance plans through algorithm calculation and software analysis, analyze the mechanisms and causes of the equipment failures identified in railway maintenance, and estimate and predict failure rates based on the failure mode modeling, and enable dynamic adjustment of patrol inspection plans. In addition, by collecting field data for empirical analysis, this system can assess the resulting patrol inspection plans for rationality. Revealed in an application case, the patrol inspection plans generated on the basis of the proposed solution enabled 4 rounds of patrol inspection before a majority of failures occurred, accounting for 89.1%, among which the first and second rounds and the third round were finished by 100% and 97.4% respectively before occurrence of any failure, equivalent to a reduction of 35% patrol inspection and 46% auxiliary repair and minor repair. It is fully demonstrated that the intelligent patrol inspection system can improve efficiency and reduce costs of inspection and maintenance, offering significant potential for upgrading the ability of equipment inspection and maintenance.